Entrepreneurship in Culture and Creative Industries Perspectives from Companies and Regions (FGF Studies in Small Business and Entrepreneurship,, 2018)
This book explains and analyzes entrepreneurship and cultural management issues in the creative and cultural sectors and discusses the impacts of economic, social and structural changes on cultural entrepreneurship. The expert contributions investigate the role of cultural entrepreneurship in regional and destination management and development by presenting best practice examples. It offers various interdisciplinary approaches, including perspectives from the fields of entrepreneurship and management, regional and destination management and development, sociology, psychology, innovation as well as creative industries, and also features articles exploring cultural entrepreneurship on a corporate as well as on a spatial level - or in other words in regions and destinations. .